Analysis of 7th-grade Students' Misconceptions of Acid-Base - Panggabean, Freddy Tua Musa; Simanjuntak, Lia Angraini; Sihombing, Rizky Agassy; Octavia, Sherly Christina; Tambunan, Jenita Br. (J-PEK (Jurnal Pembelajaran Kimia), 2023)
In the classroom, students have several barriers that affect learning outcomes and learning experiences. Generally, the obstacles that occur are the misconceptions experienced by students. Teachers' error causes many students to have misconceptions about the concept and lack practice questions related to the idea. This research was conducted to see and describe the students' misconceptions about understanding acids, bases and salts. This descriptive research uses test questions about acids, bases and salts and uses the CRI method to analyze data. The results show that students who lack understanding are 13.83%, good understanding 18.68%, and students with misconceptions 67.49%.